Environmental variation impacts trait expression and selection in the legume–rhizobium symbiosis. Issue 2 (16th February 2020) - Batstone, Rebecca T.; Peters, Madeline A. E.; Simonsen, Anna K.; Stinchcombe, John R.; Frederickson, Megan E.
Abstract : Premise: The ecological outcomes of mutualism are well known to shift across abiotic or biotic environments, but few studies have addressed how different environments impact evolutionary responses, including the intensity of selection on and the expression of genetic variance in key mutualism‐related traits. Methods: We planted 30 maternal lines of the legume Medicago lupulina in four field common gardens and compared our measures of selection on and genetic variance in nodulation, a key trait reflecting legume investment in the symbiosis, with those from a previous greenhouse experiment using the same 30 M. lupulina lines. Results: We found that both the mean and genetic variance for nodulation were much greater in the greenhouse than in the field and that the form of selection on nodulation significantly differed across environments. We also found significant genotype‐by‐environment (G × E) effects for fitness‐related traits that were generated by differences in the rank order of plant lines among environments. Conclusions: Overall, our results suggest that the expression of genotypic variation and selection on nodulation differ across environments. In the field, significant rank‐order changes for plant fitness potentially help maintain genetic variation in natural populations, even in the face of directional or stabilizing selection.